TEACHER'S ASSESSMENT LITERACY: AN ANALYSIS OF MULTIPLE CHOICE TEST QUESTIONS OF A JUNIOR HIGH SCHOOL'S EFL LEARNERS - Shabir, Muhammad (ENGLISH JOURNAL, 2018)
Stick to the required rules and standards of multiple choice test assessment, the study seeks to analyze the multiple choice test questions administered for Indonesian EFL learners at a junior high school. A careful analysis was given to the items of a summative multiple choice of English midterm test. Using the classical test theory (CTT) in analyzing each test item, it was found that only 23 percent of the total of the analyzed items are acceptable or have adopted the standards or the rules required. There are two identified major problems or causes to the poor quality of the test: distractor plausibility and limitedness in the number of possible options or distractors. To deal with the problems, the study suggests the using of fewer possible options or alternatives for such test for better assessment.